THE SIGNIFICANCE OF COASTAL YOUTH EDUCATION IN THE DEVELOPMENT OF MANGROVE ECOTOURISM THROUGH P.A.R. STRATEGY FOR THE CONSERVATION OF API MOUNT COASTAL RESOURCES, BANDA ISLANDS - Restiani, Restiani; Ohorella, Munira; Wongsopatty, Karto (Faculty of Administrative Science, Universitas Brawijaya, 2026)
Mangrove ecotourism development is a strategic effort to maintain coastal ecosystem sustainability while improving local community welfare in areas with high ecological potential but embryonic managerial systems. This study aims to analyze the condition of the mangrove ecosystem and tourism management, identify key challenges, and formulate sustainable development strategies in Kalombo District, Nusantara Village, Banda District, Central Maluku Regency. This research employed a qualitative descriptive approach using the Participatory Action Research (PAR) method. Data were collected through observation, in-depth interviews with 35 purposively sampled respondents, questionnaires, and Focus Group Discussions (FGD). Data analysis followed the interactive model of Miles, Huberman, and Saldaña. Results indicate that the ecosystem is well-preserved with seven major mangrove species, yet management faces challenges such as weak institutional structures, limited human resource capacity, and minimal educational infrastructure. Development strategies were formulated based on S.M.A.R.T. principles, focusing on strengthening permanent institutions, community training, and integrating conservation with the local economy. In conclusion, the success of this ecotourism depends on transforming the community into independent management actors through community-based empowerment.